Neuroendocrine and Inflammatory Responses to Losartan and Continuous Positive Airway Pressure in Patients with Hypertension and Obstructive Sleep Apnea A Randomized Controlled Trial - (:unkn) unknown (AMER THORACIC SOC, 2016)
Rationale: Blood pressure reduction in response to antihypertensive agents is less for patients with obstructive sleep apnea (OSA). Increased sympathetic and inflammatory activity, as well as alterations in the renin-angiotensin-aldosterone system, may play a role in this context. Objectives: To address the cardiovascular mechanisms involved in response to an angiotensin II receptor antagonist, losartan, and continuous positive airway pressure (CPAP) as add-on treatment for hypertension and OSA. Methods: Newly diagnosed hypertensive patients with or without OSA (allocated in a 2: 1 ratio for OSA vs. no OSA) were treated with losartan 50 mg daily during a 6-week two-center, open-label, prospective, case-control, parallel-design study. In the second 6-week, sex-stratified, open-label, randomized, parallel-design study, all subjects with OSA continued to receive losartan and were randomly assigned to either CPAP as add-on therapy or to no CPAP (1: 1 ratio for CPAP vs. no CPAP). Study subjects without OSA were followed in parallel while they continued to take losartan. Blood samples were collected at baseline, after 6 weeks, and after 12 weeks for analysis of renin, aldosterone, noradrenaline, adrenaline, and inflammatory markers. Measurements and Main Results: Fifty-four patients with OSA and 35 without OSA were included in the first 6-week study. Losartan significantly increased renin levels and reduced aldosterone levels in the group without OSA. There was no significant decrease in aldosterone levels among patients with OSA. Add-on CPAP treatment tended to lower aldosterone levels, but reductions were more pronounced in measures of sympathetic activity. No significant changes in inflammatory markers were observed following treatment with losartan and CPAP. Conclusions: Hypertensive patients with OSA responded to losartan treatment with smaller reductions in aldosterone compared with hypertensive patients without OSA. Sympathetic system activity seemed to respond primarily to add-on CPAP treatment in patients with newly discovered hypertension and OSA.
Keywords: hypertension; sleep apnea; obstructive; losartan; continuous positive airway pressure; randomized controlled trial; RESISTANT HYPERTENSION; SYMPATHETIC ACTIVITY; ENDOTHELIAL DYSFUNCTION; SYSTEMIC HYPERTENSION; INTERMITTENT HYPOXIA; PLASMA-ALDOSTERONE; BLOOD-PRESSURE; THERAPY; SEVERITY; MARKERS